Creative labour regulation : indeterminacy andpProtection in an uncertain world - McCann, Deirdre; Lee, Sangheon, 1967-; Belser, Patrick; Fenwick, Colin; Howe, John; Luebker, Malte; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The volume is at the forefront of the academic and policy debates on effective labour regulation, offering innovative approaches to research and policy. It is an interdisciplinary response to the central challenges that face modern labour regulation and draws on contributions by leading experts in a range of disciplines.
Keywords: Personnel management; Political economy; Public finance; Economic policy; Labor economics; Development economics